Development of social entrepreneurship in the republic of Tatarstan: Population attitude - Khairullina, Yulduz Rakibovna; Garipova, Regina Rafisovna; Sattarov, Timurbek Adylovich (Linguistics and Culture Review, 2021)
The article examines the phenomenon of social entrepreneurship, its author's interpretation is given, taking into account foreign and domestic research on the problem. They analyze the evolution of social entrepreneurship in the Republic of Tatarstan, its organizational and legal support, the forms and practices of NGOs in the region. The article presents the results of the author's comprehensive empirical research (Republic of Tatarstan, 2020): a mass survey of the population, revealing its attitude to the practices of social entrepreneurship in the republic and semi-formalized interviews with government officials, socially oriented non-profit organizations, public organizations, giving a picture of opinions and assessments concerning the problems and features of the non-profit social sector operation in the regional economy. They concluded that socially oriented non-profit organizations and social entrepreneurship in the republic are actively developing and maintain a high level of service provision. There is an active interaction of various state, administrative and public structures with the institutions of social entrepreneurship in the region, there are various programs to support the activities of NGOs, a special regional model of public-state partnership is being developed in this socio-economic sphere.